THE EFFECT OF GAMIFICATION-BASED MEDIA USE ON STUDENTS' LEARNING OUTCOMES IN THE SCIENCE SUBJECT OF GRADE IV OF STATE ELEMENTARY SCHOOL 040538 SAMPUN - Tarigan, Maysela Br; Muliani, Eti; Keliat, Johannes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the continued dominance of conventional learning in science in grade IV at SD Negeri 040538 Sampun, which leads students to be passive and results in suboptimal learning outcomes. Preliminary data show that in grade IVA, only 8 out of 20 students achieved mastery, while in grade IVB, only 7 out of 17 students completed. Therefore, this study aims to analyze the effect of gamification-based media on student learning outcomes in science. This study uses a quantitative approach with a quasi-experimental design and a Nonequivalent Control Group Design. The study population comprised all 37 grade IV students, with 20 students in the experimental class and 17 in the control class. Data were collected through tests, observations, and documentation, and then analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Levene homogeneity test, and the independent-samples t-test. The results showed that the experimental class's average posttest score was 91.75, higher than the control class's 74.71. The hypothesis test showed a significance value of 0.000 < 0.05, indicating a significant effect of gamification-based media on student learning outcomes. Thus, gamification-based media is effective in improving elementary school students' science learning outcomes.